Trends in the Diagnosis and Treatment of Chronic Hepatitis B in Karachi, Pakistan - Anjum, Fakhsheena; Ghayas, Sana; Shafi, Viqas; Bashir, Lubna; Naz, Shazia (Journal of Medicine, 2013)
Aims: Aim of this study was to analyze diagnostic and therapeutic trends of physicians regarding Chronic Hepatitis B (CHB) in Karachi since Pakistan is endemic area for viral hepatitis B. Methods: A questionnaire was distributed to about 100 physicians / doctors in different hospitals of Karachi. The questionnaire assessed diagnostic trends, prescribing habits for Chronic Hepatitis B (CHB) treatment and patients monitoring and follow ups by the physician. Results: About 100 doctors from Karachi participated in the study (response rate: 72%). 34.72% doctors had experience of treating less than 10 patients per month. Majority of the doctors (79.16%) used HBsAg (anti-HBsAg seroconversion), (61.11%) used liver function tests (LFTs) and hepatitis B virus (HBV) DNA levels were used by doctors (47.22%) as diagnostic parameters for CHB. HBV-DNA levels were the most commonly used parameter to confirm diagnosis and was used by 86.11 % doctors. Treatment of CHB was started upon various indications i.e. 58.33% doctors used HBV DNA level when it is e20,000 IU/mL (105 copies/mL) ; 36.11% used HBV DNA when it is e 2000 IU/mL (104 copies/mL) and 29.16% doctors used Serum alanine aminotransferase (ALT) when it was elevated for 3-6 months. Most of the doctors (38.88%) had experience with Interferon alfa and Pegylated IFN-a 2a, (26.38%) with Lamivudine and (25%) with Entecavir. For treatment, 41.66% of doctors recommended Pegylated IFN-a 2a for HBeAg positive CHB patients whereas 22.22% of doctors treated HBeAg negative CHB Patients with Entecavir. HBV DNA levels and alanine aminotransferase (ALT) levels were most commonly used to monitor therapy by 73.61% and 52.77% doctors respectively. Frequency of follow-up was after 3 months by most of the doctors (63.88%). According to 23.61% doctors, 5 to 10% of patients required add- on treatment or switching from the previous regimen. According to most doctors (68.05%), polymerase chain reaction (PCR) - negativity was an important indication of improved response and outcome to anti-viral therapy. Conclusion: CHB management decision varies from physicians perspective and is not always based on scientific decision. Mostly doctors used HBV DNA level as indication for treatment when it is e 2000 IU/mL (104 copies/mL) and prescribed Interferon alfa and Pegylated IFN-a 2a to their patients. Monitoring of therapy was usually done by observing HBV DNA levels and alanine aminotransferase (ALT) levels of patients and frequency of follow-up was after 3 months by most of the doctors. Add- on treatment or switching is also required by some patients and improved response to treatment was assessed by PCR negativity. Management of CHB can be improved through CME (continual medical education) and practical training. DOI: http://dx.doi.org/10.3329/jom.v14i1.14538 J MEDICINE 2013; 14 : 57-61